2017
DOI: 10.1177/1744806917706582
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of microRNA-223 on morphine analgesic tolerance by targeting NLRP3 in a rat model of neuropathic pain

Abstract: ObjectiveTo investigate the effects of microRNA-223 on morphine analgesic tolerance by targeting NLRP3 in a rat model of neuropathic pain.MethodsOur study selected 100 clean grade healthy Sprague-Dawley adult male rats weighing 200 to 250 g. After establishment of a rat model of chronic constriction injury, these rats were divided into 10 groups (10 rats in each group): the normal control, sham operation, chronic constriction injury, normal saline, morphine, miR-223, NLRP3, miR-223 + morphine, NLRP3 + morphine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 41 publications
2
21
0
Order By: Relevance
“…Specifically, we demonstrated that the downregulation of miR-223 was closely associated with increased NLRP3 mRNA levels. This finding effectively supports the hypothesis that miR-223 acts as a negative regulator of NLRP3 inflammasome activity, as it was already observed in other pathological conditions (27,29). It is well recognized that NLRP3 is an important mediator involved in cell necroptosis (30), and it has been suggested that its activation may be modulated by Casp-8 (23,26).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Specifically, we demonstrated that the downregulation of miR-223 was closely associated with increased NLRP3 mRNA levels. This finding effectively supports the hypothesis that miR-223 acts as a negative regulator of NLRP3 inflammasome activity, as it was already observed in other pathological conditions (27,29). It is well recognized that NLRP3 is an important mediator involved in cell necroptosis (30), and it has been suggested that its activation may be modulated by Casp-8 (23,26).…”
Section: Discussionsupporting
confidence: 89%
“…These miRNAs have the ability to bind to their target Casp-8 mRNA transcript in order to facilitate the necroptosis of HCC cells. Additionally, the data presented herein confirm the well-known association between miR-223 and NLRP3, as already reported in different disease contexts (27)(28)(29)(30)(31).…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…For instance, by regulating voltage‐gated potassium channels, miR‐17‐92 cluster can induce chronic neuropathic pain development (Sakai et al, ). miR‐223 could inactivate NLRP3 inflammasomes to relieve neuropathic pain (Xie et al, ). miR‐30b is able to attenuate neuropathic pain progression by targeting voltage‐gated sodium channel Nav1.3 in rat models (Su et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the absence of research on interaction between DEX and NLRP3, involvement of NLRP3 has been intensively investigated in research on neuropathic pain. For instance, microRNA-223 ameliorated morphine analgesic tolerance to neuropathic pain by down-regulating NLRP3 [21]. Paclitaxel activated neuropathic pain by stimulating NLRP3 in ammasome and pro-in ammatory factor IL-1β [22].…”
Section: Discussionmentioning
confidence: 99%